Effect of sertraline on central serotonin and hippocampal plasticity in pregnant and non-pregnant rats. (April 2020) - Pawluski, Jodi L.; Paravatou, Rafaella; Even, Alan; Cobraiville, Gael; Fillet, Marianne; Kokras, Nikolaos; Dalla, Christina; Charlier, Thierry D.
Abstract: One of the most frequently prescribed selective serotonin reuptake inhibitor medications (SSRIs) for peripartum mood and anxiety disorders is sertraline (Zoloft®). Sertraline can help alleviate mood and anxiety symptoms in many women but it is not known how sertraline, or SSRIs in general, affect the neurobiology of the brain particularly when pregnant. The aim of this study was to investigate how sertraline affects plasticity in the hippocampus, a brain area integral in depression and SSRI efficacy (particularly in males), during late pregnancy and whether these effects differ from the effects of sertraline in non-pregnant females. To do this pregnant and age-matched non-pregnant female Sprague-Dawley rats were used. For the last half of pregnancy (10 days), and at matched points in non-pregnant females, rats were given sertraline (2.5 mg/kg/day or 10 mg/kg/day) or vehicle (0 mg/kg/day). Brains were used to investigate effects on the serotonergic system in the hippocampus and prefrontal cortex and measures of neuroplasticity in the hippocampus. Results show that pregnant females have significantly higher serum levels of sertraline compared to non-pregnant females but that rates of serotonin turnover in the hippocampus and PFC are similar between pregnant and non-pregnant females. Sertraline increased synaptophysin density in the dentate gyrus and CA3 and was associated with a decrease in cell proliferation in the dentate gyrus of non-pregnant, but not pregnant, females. During late pregnancy the hippocampus showed significant reductions in neurogenesis and increases in synaptophysin density. This research highlights the need to consider the unique effect of reproductive state on the neuropharmacology of SSRIs. Highlights: Pregnancy does not alter sertraline effects on serotonin in HPC or PFC. Sertraline increases synaptophysin in DG and CA3 when non-pregnant. Pregnancy increases synaptophysin in DG and CA3. Hippocampal neurogenesis is decreased during late pregnancy. Need to consider reproductive state on neuropharmacological effects of SSRIs.